DEVELOPMENT OF SIMPLE PROMOTIONAL TOOLS BASED ON RECYCLING ON THE BLOOD CIRCULATORY SYSTEM MATERIAL IN ELEMENTARY SCHOOLS - Kesumawati, Diah; Puji Anggraini, Dini (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2025)
This study aiming for develop tool props simple based on recycle repeat. Type study that is research and development (RD). This study using the 4D development model consists of from define, design, develop and disseminate (Thiagarajan., 1974). This research only up to the development stage. This research implemented at SD IT Bintang Langkat. Subject study that is student class V consisting of 25 students. Object study that is tool props simple based on recycle repeat. The data collection technique is observation, interviews, tests, and questionnaires. Data analysis techniques used namely (a) eligibility book story illustrated, and (b) effectiveness book story illustrated. Based on results study known that tool props simple based on recycle redeveloped declared very worthy, thing this based on results validation by experts material that is with percentage 87.50%, result validation by experts Language with percentage of 79.35% stated worthy, and results validation by media experts with the percentage of 90.68% was declared very feasible. From the results recapitulation said, it was concluded that tool props simple based on recycle repeat declared very worthy for used on students fifth grade at Bintang Langkat IT Elementary School.